(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vietnam government considers inflation adjustment as a primary goal of policies planning and implementing to achieve economic stability and GDP growth. Therefore, defining the threshold in inflation-GDP growth relationship is an important task to propose target inflation rate precisely. This paper investigates the threshold between inflation and GDP growth in Vietnam. Inflation is assumed to have a nonlinear relationship with GDP growth. The results confirm the existence of the threshold at 6 per cent inflation point, and the negative impacts on GDP growth of hyperinflation above the threshold and too low inflation beyond the threshold. Taking into account the total impact of inflation on GDP growth, the effects are negative. This finding suggests that Vietnam authorities should target lower inflation of 6 per cent to improve GDP growth.